2016
DOI: 10.1111/joid.12067
|View full text |Cite
|
Sign up to set email alerts
|

Is Seeing Intriguing? Practitioner Perceptions of Research Documents

Abstract: Although design practitioners have a myriad of information sources available, they often have little time to evaluate the information. The need to study visual persuasive tactics is highlighted by (1) the propensity of designers to use visual communications, (2) the availability of sources that range in validity, (3) work stressors encountered by designers, and (4) the benefits of using peer‐reviewed sources. Given these contexts, it may behoove design scholars to acknowledge the constraints and desires of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…The human element of participating in data visualization is key (Segel and Heer ). Interactivity is believed to improve information processing and contribute to increased engagement (Grainger, Mao, and Buytaert ; Huber ; Li and Liu ; Segel and Heer ). This allows users to choose which aspects of the information to explore, which increases their enjoyment and essentially invites them to “join the process” (Huber ).…”
Section: Visualization Is Thought To Enhance Comprehension Through Enmentioning
confidence: 99%
See 2 more Smart Citations
“…The human element of participating in data visualization is key (Segel and Heer ). Interactivity is believed to improve information processing and contribute to increased engagement (Grainger, Mao, and Buytaert ; Huber ; Li and Liu ; Segel and Heer ). This allows users to choose which aspects of the information to explore, which increases their enjoyment and essentially invites them to “join the process” (Huber ).…”
Section: Visualization Is Thought To Enhance Comprehension Through Enmentioning
confidence: 99%
“…Interactivity is believed to improve information processing and contribute to increased engagement (Grainger, Mao, and Buytaert ; Huber ; Li and Liu ; Segel and Heer ). This allows users to choose which aspects of the information to explore, which increases their enjoyment and essentially invites them to “join the process” (Huber ). For example, on the autism website detailed later, viewers can choose which aspects of the data to explore and which to skim or skip all together—the depth of information is revealed based on interest.…”
Section: Visualization Is Thought To Enhance Comprehension Through Enmentioning
confidence: 99%
See 1 more Smart Citation
“…While literature lacks recent studies exploring the decision‐making processes of designers when making human capital decisions, studies have suggested that designers call on rapid information processes during the design process (Gray, Seifert, Yilmaz, Daly, & Gonzalez, ; Yilmaz & Seifert, ) and when reviewing information under time constraints (Huber, , , ). Given that over one in four of Huber and Pable's () hiring practitioner respondents received over 50 applicants for a typical entry‐level interior design job opening, one might infer that the time allocated to each candidate's package is relatively limited, and consequently, heuristics may factor heavily into these initial assessments.…”
Section: Literaturementioning
confidence: 99%
“…). However, even the most logical messages remain dependent on the audience for interpretation and their persuasiveness depends on the motivation and ability of an audience to process the evidence (Petty & Cacioppo ), and the perceived attractiveness of the messenger (Chaiken ; Watkins & Johnston ) or the message itself (Huber ).…”
Section: Aristotle's Rhetorical Frameworkmentioning
confidence: 99%